Studi Komparasi Perilaku Wisatawan Nusantara Generasi-X dan Milenial Era Revolusi Industri 4.0 di Indonesia - Dina Mayasari Soeswoyo; Sekti Rahardjo (STIEPAR YAPARI Bandung, 2020)
The rapid development of the tourism industry in Indonesia has also contributed to the intense level of competition among tourism destination and their supporting industries. Marketers are required to be smarter in determining the promotion tool and marketing strategies of their businesses. This survey research aims to improve understanding of the characteristics and travelling behavior from two different market segments namely Generation X (born 1965-1980) and Generation Y or Millennial Generation (born 1981-2000). Data collection techniques were carried out by triangulation, namely literature review, questionnaires and interviews face to face directly and through WhatssApp. The sample of respondents used was 162 Gen-X and 244 Gen-Y selected purposively, by distributing questionnaires during February 2020 to visitors who have traveled to the city of Bogor. Data analysis was performed descriptively qualitative. The result from this survey research in this case study is that Gen-X and Gen-Y have many similarities in terms of characteristics and travel behavior. Significant differences in the two generations are in the 3 attributes of Respondent Characteristics (gadget usage time per day, social media preferences used, travel budget) and Travel Behavior in the aspects of Initiation, Decision Making, When Traveling and Post-Traveling.